Perovskite solar cell and method of manufacturing the same

CN122952853APending Publication Date: 2026-10-20GUANGDONG GUANGJING ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611438992.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种钙钛矿太阳能电池及其制备方法,以解决现有技术中具有钝化层的钙钛矿太阳能电池制备工艺复杂且设备成本较高的问题

Benefits of technology

1.高效空穴阻挡:BCP具有深HOMO能级(约-6.0eV),能有效阻挡空穴到达阴极,防止电子-空穴在金属电极50界面复合,显著提升开路电压(VOC)和填充因子(FF)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the field of perovskite solar cell technology. It discloses a perovskite solar cell and its fabrication method. In the fabrication method, a passivation / charge transport composite layer is obtained by directly mixing a passivation solution with a first charge transport layer solution and directly coating it onto the surface of the perovskite absorber layer. This simplifies the traditional two-step fabrication process into a single step. Furthermore, the thickness of the charge transport layer can be selected by adjusting the solution concentration and coating process, significantly reducing solution costs and enabling large-area fabrication. Therefore, it significantly improves fabrication efficiency, reduces equipment investment, and lowers production and site costs. In addition, by directly coating the passivation / charge transport composite layer onto the surface of the perovskite absorber layer, unsaturated lead sites in the passivation material can be used to precisely repair surface defects, thereby eliminating deep-level traps, improving structural stability, extending carrier lifetime, and enhancing photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of perovskite solar cell technology, and in particular to a perovskite solar cell and its fabrication method. Background Technology

[0002] Perovskite materials have strong light absorption, adjustable band gap, and can be prepared in low-temperature solutions. Over the past decade, their efficiency has rapidly increased to around 27%. They also have the advantages of being lightweight, flexible, and low-cost. However, reliable and scalable methods are still needed to manufacture large-area solar panels and commercialize this emerging photovoltaic technology.

[0003] Wet preparation primarily utilizes liquid-phase processes such as blade coating and slot coating, offering significant advantages. Firstly, raw materials and equipment costs are low, eliminating the need for high-vacuum and high-temperature equipment. The overall energy consumption of this preparation process is far lower than that of crystalline silicon and vapor deposition processes, making it suitable for large-area mass production. Secondly, component control is flexible; by adjusting the precursor solution ratio and concentration, the perovskite band gap and crystal morphology can be precisely controlled, easily yielding high-quality light-absorbing layers.

[0004] However, due to the inherent defects of the perovskite absorber layer, a perovskite passivation layer is required to protect it. Therefore, both the fully wet fabrication of non-in-line (NIP) and inverted (PIN) structure components require at least four functional layers: a first charge transport layer, a perovskite absorber layer, a perovskite passivation layer, and a second charge transport layer. This results in high equipment costs and complex fabrication processes. Summary of the Invention

[0005] The main objective of this application is to provide a perovskite solar cell and its preparation method, so as to solve the problems of complex preparation process and high equipment cost of perovskite solar cells with passivation layer in the prior art.

[0006] In a first aspect, this application provides a method for fabricating a perovskite solar cell, the method comprising the following steps:

[0007] A mixed solution precursor is obtained by mixing the passivation solution with the first charge transport layer solution. The mixed solution precursor is coated onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer.

[0008] In the embodiments of this application, the passivation / charge transport composite layer is a passivation / hole transport composite layer; The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: The organic ammonium bromide salt was dissolved in isopropanol solvent, and the solution was shaken to dissolve it, resulting in a passivation solution with a concentration of 30-60 mg / mL. Spiro-OMeTAD or PTAA was dissolved in anisole or chlorobenzene solvent, and the solution was shaken to dissolve, resulting in a hole transport layer solution with a concentration of 20-100 mg / mL. The prepared passivation solution was added to the prepared hole transport layer solution at a concentration of 0.5 mg / mL-5 mg / mL, and the mixture was shaken to dissolve, thus obtaining the mixed solution precursor.

[0009] In the embodiments of this application, the passivation / charge transport composite layer is a passivation / electron transport composite layer; The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: The organic ammonium bromide salt was dissolved in isopropanol solvent, and the solution was shaken to dissolve it, resulting in a passivation solution with a concentration of 30-60 mg / mL. [6,6]-phenyl C61 butyrate methyl ester (PC61BM) was dissolved in chlorobenzene solvent, and the solution was shaken to obtain an electron transport layer solution with a concentration of 20-40 mg / mL. The prepared passivation solution was added to the prepared electron transport layer solution at a concentration of 0.5 mg / mL-5 mg / mL, and the mixture was shaken to dissolve, thus obtaining the mixed solution precursor.

[0010] In embodiments of this application, the step of coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer includes: The mixed solution precursor is added to a slot coater, and the mixed solution precursor is uniformly coated onto the surface of the perovskite absorber at a coating speed of 5-20 mm / s and an outflow rate of 10-20 μL / s. After the solvent evaporates, a composite solution semi-wet film is obtained. The slot width of the slot coater is 80-150 μm, and the area of ​​the perovskite absorber is greater than or equal to 300 μm. 300mm; The semi-finished product coated with the composite solution semi-wet film is placed on a hot plate at 130-150°C and annealed for 5-10 minutes to obtain a passivation / charge transport composite layer stacked on the surface of a large-area perovskite absorber layer, wherein the total thickness of the perovskite absorber layer and the passivation / charge transport composite layer is 500nm-560nm.

[0011] In the embodiments of this application, the organic ammonium bromide salt is selected from any one of isobutylammonium bromide (i-BABr), phenylethylammonium bromide (PEABr), diamine dihydrobromide (DABr), 2-(1-cyclohexenyl)ethylamine hydrobromide (CHEABr), methylammonium bromide (MABr), tetrabutylammonium bromide (TBAB), phenylpropylammonium bromide (PPAABr), and butylammonium bromide (BABr).

[0012] In embodiments of this application, before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate that has been scribing with P1. The second charge transport layer solution is uniformly coated onto the surface of the transparent conductive substrate using a slit coating process to obtain an electron transport layer. The perovskite precursor is uniformly coated on the surface of the electron transport layer using a slot coating process to obtain the perovskite absorption layer. And / or, after the preparation method involves coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer, the preparation method further includes the following steps: Perform P2 marking on the above semi-finished products; A metal electrode is sputtered onto the passivation / charge transport composite layer; P3 scribing is performed on the metal electrode.

[0013] In embodiments of this application, preparing a clean and dry transparent conductive substrate after P1 scribing includes: Prepare a transparent conductive substrate; A P1 line scribing process is performed on the transparent conductive substrate; The transparent conductive substrate is cleaned by immersing it in deionized water containing a cleaning agent; The transparent conductive substrate is rinsed in deionized water. The transparent conductive substrate was ultrasonically cleaned in ethanol for 13-17 minutes. The transparent conductive substrate was dried using a nitrogen gun. And / or, the step of uniformly coating the second charge transport layer solution onto the surface of the transparent conductive substrate using a slit coating process to obtain an electron transport layer includes: Add 5g of urea to 400ml of pure water and sonicate to obtain a urea solution, wherein the resistance of the pure water is greater than 18MΩ. 100 μl of mercaptoacetic acid, 5 ml of concentrated hydrochloric acid (37 wt%) and 1.096 g of stannous chloride dihydrate were added to the urea solution in sequence and mixed evenly to obtain a tin dioxide solution. Refrigerate the tin dioxide solution for 6-48 hours. The electron transport layer solution was obtained by diluting 200 μl of tin dioxide solution with 1 ml of pure water. The electron transport layer solution is uniformly coated onto the surface of the transparent conductive substrate using a slit coating process to obtain a semi-wet electron transport layer film. The semi-finished product coated with the electron transport layer semi-wet film is annealed to obtain an electron transport layer stacked on the surface of a transparent conductive substrate. And / or, the process of uniformly coating the perovskite precursor onto the surface of the electron transport layer using a slot coating process to obtain the perovskite absorber layer includes: The perovskite precursor is uniformly coated on the surface of the electron transport layer using a slot coating process to obtain a semi-wet perovskite absorber layer. The perovskite absorber layer is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer. And / or, the thickness of the metal electrode is between 80 nm and 120 nm.

[0014] In embodiments of this application, before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate that has been scribing with P1. A NiOx layer is sputtered onto the surface of the transparent conductive substrate, wherein the NiOx layer is a hole transport layer; The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain the perovskite absorption layer. And / or, after the preparation method involves coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer, the preparation method further includes the following steps: A BCP protective layer was prepared on the passivation / charge transport composite layer using a thermal evaporation method. Perform P2 marking on the above semi-finished products; Metal electrodes were sputtered onto the passivation / charge transport composite layer using magnetron sputtering. P3 scribing is performed on the metal electrode.

[0015] In embodiments of this application, preparing a clean and dry transparent conductive substrate after P1 scribing includes: Prepare a transparent conductive substrate; A P1 line scribing process is performed on the transparent conductive substrate; The transparent conductive substrate is cleaned by immersing it in deionized water containing a cleaning agent; The transparent conductive substrate is rinsed in deionized water. The transparent conductive substrate was ultrasonically cleaned in ethanol for 13-17 minutes. The transparent conductive substrate was dried using a nitrogen gun. And / or, the sputtering of a NiOx layer on the surface of the transparent conductive substrate, wherein the NiOx layer is a hole transport layer, includes: Using oxygen as the sputtering gas, NiOx material is obtained by reactive sputtering of a metallic nickel target under both DC and RF methods. The sputtering time is controlled to obtain a hole transport layer of target thickness deposited on the transparent conductive substrate. And / or, the step of uniformly coating the perovskite precursor onto the surface of the hole transport layer using a slot coating process to obtain the perovskite absorber layer includes: The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain a semi-wet perovskite absorber layer. The perovskite absorber layer is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer. And / or, the thickness of the BCP protective layer is between 5nm and 10nm; And / or, the thickness of the metal electrode is between 80 nm and 120 nm.

[0016] Secondly, this application also provides a perovskite solar cell, which is prepared using the perovskite solar cell preparation method described in any of the above claims.

[0017] In the perovskite solar cell fabrication method of this application, a mixed solution precursor is obtained by directly mixing a passivation solution with a first charge transport layer solution. The mixed solution precursor is then directly coated onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer. This simplifies the traditional two-step fabrication process into a single step. Furthermore, the thickness of the charge transport layer can be selected by adjusting the solution concentration and coating process, significantly reducing solution costs and enabling large-area fabrication. Therefore, fabrication efficiency is significantly improved, equipment investment is reduced, and production costs such as labor, equipment, and space are lowered. In addition, by directly coating the passivation / charge transport composite layer onto the surface of the perovskite absorber layer, unsaturated lead sites in the passivation material can be used to precisely repair surface defects, thereby eliminating deep-level traps, improving structural stability, extending carrier lifetime, suppressing ion migration, and enhancing photoelectric conversion efficiency. Attached Figure Description

[0018] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic SEM cross-sectional view of a formal perovskite solar cell in one embodiment of this application.

[0019] Figure 2This is a SEM image of the surface grain distribution of the passivation layer of a formal perovskite solar cell in one embodiment of this application. The SEM image is obtained by SEM scanning after the passivation / hole transport composite layer is prepared on the perovskite absorber layer, the hole transport layer is dissolved in a solvent, and the passivation layer is left on the upper surface of the perovskite absorber layer.

[0020] Figure 3 The image shows a SEM image of the surface grain distribution of the perovskite absorber layer in the formal perovskite solar cell of Comparative Example 1. In Comparative Example 1, the perovskite absorber layer was not passivated.

[0021] Figure 4 The image shows a SEM image of the surface grain distribution of the passivation layer in the formal perovskite solar cell of Comparative Example 2, in which the perovskite absorber layer was passivated separately.

[0022] Figure 5 This is a JV curve of a single sub-cell in a formal perovskite solar cell module disclosed in this application, wherein the area of ​​a single sub-cell is 0.15 cm².

[0023] Figure 6 This is a JV curve diagram of the entire perovskite solar cell module in one embodiment of this application, wherein the area of ​​the entire module is 900 cm².

[0024] Figure 7 The diagram shows the PL of the formal perovskite solar cell in Comparative Example 1.

[0025] Figure 8 The diagram shows the PL of the formal perovskite solar cell in Comparative Example 2.

[0026] Figure 9 This is a PL diagram of a formal perovskite solar cell in one embodiment disclosed in this application.

[0027] The above figures include the following reference numerals: The perovskite solar cell 100 consists of a transparent conductive substrate 10, an electron transport layer 20, a perovskite absorber layer 30, a passivation / hole transport composite layer 40, and a metal electrode 50. Detailed Implementation

[0028] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.

[0029] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0030] Unless otherwise specifically stated, the relative arrangement, numerical expressions, and values ​​of the components and steps described in these embodiments do not limit the scope of this application. It should also be understood that, for ease of description, the dimensions of the various parts shown in the drawings are not drawn to actual scale. Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters in the following drawings denote similar items; therefore, once an item is defined in one drawing, it need not be further discussed in subsequent drawings.

[0031] Please see Figure 1-9 As shown, in a first aspect, this application provides a method for fabricating a perovskite solar cell 100, the method comprising the following steps: The passivation solution is mixed with the first charge transport layer solution to obtain a mixed solution precursor.

[0032] The mixed solution precursor is coated onto the surface of the perovskite absorber layer 30 to obtain a passivation / charge transport composite layer.

[0033] In the perovskite solar cell 100 fabrication method of this application, a mixed solution precursor is obtained by directly mixing a passivation solution with a first charge transport layer solution, and the mixed solution precursor is directly coated onto the surface of the perovskite absorber layer 30 to obtain a passivation / charge transport composite layer. This simplifies the traditional two-step fabrication process into one step. At the same time, the thickness of the charge transport layer can be selected by the solution concentration and coating process, which significantly reduces the cost of using solutions and enables large-area fabrication. Therefore, the fabrication efficiency is significantly improved, equipment investment is reduced, and production costs such as labor, equipment, and site are lowered. In addition, by directly coating the passivation / charge transport composite layer onto the surface of the perovskite absorber layer 30, the ion-bonded unsaturated lead sites in the passivation material can be used to precisely repair surface defects, thereby eliminating deep-level traps and improving structural stability, extending carrier lifetime, suppressing ion migration, and improving photoelectric conversion efficiency.

[0034] Please see Figure 1 As shown in the embodiments of this application, the passivation / charge transport composite layer is a passivation / hole transport composite layer 40. Therefore, the perovskite solar cell 100 has a formal structure, that is, the perovskite solar cell 100 includes a transparent conductive substrate 10, an electron transport layer 20, a perovskite absorber layer 30, a passivation / hole transport composite layer 40, and a metal electrode 50 stacked sequentially.

[0035] The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: The organic ammonium bromide salt was dissolved in isopropanol solvent, and the solution was shaken to dissolve, resulting in a passivation solution with a concentration of 30-60 mg / mL.

[0036] The concentration of the passivation solution can be 30 mg / mL or 60 mg / mL, or any concentration between 30 and 60 mg / mL, such as 37 mg / mL, 45.2 mg / mL, 59 mg / mL, etc., which will not be listed here.

[0037] Spiro-OMeTAD or PTAA was dissolved in anisole or chlorobenzene solvent, and the solution was shaken to dissolve, resulting in a hole transport layer solution with a concentration of 20-100 mg / mL.

[0038] The concentration of the hole transport layer solution can be 20 mg / mL or 100 mg / mL, or any concentration between 20 and 100 mg / mL, such as 22 mg / mL, 29.8 mg / mL, 37 mg / mL, 45.2 mg / mL, 60 mg / mL, 77.6 mg / mL, 85 mg / mL, 97 mg / mL, etc., which will not be listed here.

[0039] The prepared passivation solution is added to the prepared hole transport layer solution at a concentration of 0.5-5 mg / mL, and the mixture is shaken to dissolve, yielding a mixed solution precursor. The concentration of the passivation solution added to the hole transport layer solution can be 0.5 mg / mL or 5 mg / mL, or any concentration between 0.5-5 mg / mL, such as 0.51 mg / mL, 0.56 mg / mL, 0.6 mg / mL, 0.68 mg / mL, 0.7 mg / mL, 1.02 mg / mL, 1.41 mg / mL, 1.85 mg / mL, 2.49 mg / mL, 2.95 mg / mL, 3.24 mg / mL, 3.84 mg / mL, 4.06 mg / mL, 4.55 mg / mL, 4.99 mg / mL, etc., and will not be listed individually here.

[0040] By coating the mixed solution precursor onto the surface of the perovskite absorber layer 30, a passivation / hole transport composite layer 40 is obtained, in which the organic ammonium cation (R-NH3) is present. + The nitrogen atom in the Pb² group provides a lone pair of electrons, which interact with the uncoordinated Lewis acidic Pb² on the surface. + Formation of strong coordination bonds. Bromide ions (Br) - It can fill halogen vacancies or react with Pb² + Coordination eliminates deep-level defects. Small-molecule ammonium bromide can penetrate into grain boundaries and even the bulk phase, repairing internal defects through top-down diffusion and achieving through-passivation.

[0041] Strong coordination bonds "lock" surface-active defect sites, preventing them from becoming starting points for degradation reactions. High-binding-energy ligands resist photothermal-induced deprotonation, avoiding ligand detachment and secondary defects.

[0042] Physical barrier effect: The two-dimensional phase or dense molecular layer generated in situ acts as a physical barrier, preventing water molecules and oxygen from entering the crystal lattice, while inhibiting the outward migration of internal halide ions or their side reactions with the electrodes.

[0043] Stress relief and lattice stability: Organic long chains can alleviate lattice thermal stress and inhibit microcrack formation. The introduction of bromide ions can adjust the lattice constant, improve the phase stability of wide-bandgap perovskites, and prevent photo-induced phase separation.

[0044] Therefore, the passivation / hole transport composite layer 40 on the upper surface of the perovskite absorber layer 30 can be prepared in one step by reacting organic ammonium with the surface PbI2-rich layer to generate a continuous two-dimensional perovskite. The outer hydrophobic organic carbon chain forms a double-layer protective barrier, which scatters the sputtered ion kinetic energy and greatly reduces the ion flux reaching the bottom 3D perovskite.

[0045] In addition, the two-dimensional perovskite organic ammonium salt uses isopropanol as the main solvent. In the large-area slot coating deposition method, the contact time is longer than in the dynamic spin coating method. If not properly adjusted, IPA can penetrate along grain boundaries, increasing roughness and causing a decrease in carrier mobility and Jsc decay. In contrast, the one-step two-in-one method uses a solvent with extremely low polarity and no hydrogen bonds, which hardly dissolves the complete 3D perovskite bulk. Isopropanol accounts for only a small proportion of this solvent, and its ability to damage the perovskite absorber layer 30 is far weaker than the damage caused by pure isopropanol in the traditional separate preparation of the passivation layer.

[0046] In embodiments of this application, the step of coating the mixed solution precursor onto the surface of the perovskite absorber layer 30 to obtain a passivation / charge transport composite layer includes: The mixed solution precursor is added to a slot coater, and the mixed solution precursor is uniformly coated onto the surface of the perovskite absorber layer 30 at a coating speed of 5-20 mm / s and a dispensing rate of 10-20 μL / s. After the solvent evaporates, a composite solution semi-wet film is obtained. The slot width of the slot coater is 80-150 μm, and the area of ​​the perovskite absorber layer 30 is greater than or equal to 300 μm. 300mm.

[0047] The coating speed can be 5 mm / s or 20 mm / s, or any speed between 5 and 20 mm / s, such as 5.1 mm / s, 5.5 mm / s, 5.9 mm / s, 6.8 mm / s, 9.4 mm / s, 11.3 mm / s, 16 mm / s, 18.5 mm / s, 19.9 mm / s, etc.

[0048] The dispensing rate can be 10 uL / s or 20 uL / s, or any dispensing rate between 10 and 20 uL / s, such as 10.1 uL / s, 10.9 uL / s, 12.5 uL / s, 14 uL / s, 16.2 uL / s, 17 uL / s, 18.8 uL / s, 19.1 uL / s, 19.9 uL / s, etc., which will not be listed here.

[0049] The slit width can be 80 μm or 150 μm, or any width between 80 and 150 μm, such as 80.1 μm, 88 μm, 92 μm, 97 μm, 100 μm, 109 μm, 115 μm, 123 μm, 138 μm, 145 μm, 149 μm, etc., which will not be listed here.

[0050] The area of ​​the perovskite absorber layer can be 300. 300mm, or 300 350mm, 350 350mm, etc., will not be listed here one by one.

[0051] This setup allows for the preparation of the mixed solution precursor in one step, and enables the preparation of a large-area passivation / charge transport composite layer with uniform thickness and stable film structure, significantly improving preparation efficiency and reducing preparation costs.

[0052] The semi-finished product coated with the composite solution semi-wet film is placed on a hot plate at 130-150°C and annealed for 5-10 minutes to obtain a passivation / charge transport composite layer stacked on the surface of a large-area perovskite absorber layer 30, wherein the total thickness of the perovskite absorber layer 30 and the passivation / charge transport composite layer is 500nm-560nm.

[0053] The annealing temperature can be 130℃ or 150℃, or any temperature between 130℃ and 150℃, such as 131℃, 135℃, 138℃, 140℃, 142℃, 146℃, 149℃, etc., which will not be listed here.

[0054] The annealing time can be 5 minutes or 10 minutes, or any time between 5 and 10 minutes, such as 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes, etc., which will not be listed here.

[0055] The total thickness can be 500nm or 560nm, or any thickness between 500 and 560nm, such as 501nm, 507nm, 510nm, 515nm, 525nm, 530nm, 540nm, 550nm, 555nm, 559nm, etc., which will not be listed here.

[0056] In embodiments of this application, before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate 10 after P1 scribing treatment, so as to prepare an electron transport layer 20 on the transparent conductive substrate 10.

[0057] The transparent conductive substrate 10 prepared after P1 scribing and being clean and dry includes: Prepare a transparent conductive substrate 10.

[0058] A P1 line scribing process is performed on the transparent conductive substrate 10.

[0059] The transparent conductive substrate 10 is cleaned in deionized water containing a cleaning agent.

[0060] The transparent conductive substrate 10 is rinsed in deionized water.

[0061] The transparent conductive substrate 10 is ultrasonically cleaned in ethanol for 13-17 minutes. The ultrasonic cleaning time of the transparent conductive substrate 10 in ethanol can be 13 min, 13.5 min, 14 min, 14.5 min, 15 min, 15.5 min, 16 min, 16.5 min, etc., and will not be listed here.

[0062] The transparent conductive substrate 10 was dried with a nitrogen gun.

[0063] Multiple deep cleanings can prevent dirt residue from remaining on the transparent conductive substrate 10 after P1 scribing. Nitrogen gun drying can quickly remove residual solvent / moisture to avoid water stains, prevent surface re-oxidation or adsorption of impurities, thereby ensuring the stability and uniformity of subsequent thin film deposition or device performance.

[0064] The second charge transport layer solution is uniformly coated on the surface of the transparent conductive substrate 10 using a slit coating process to obtain an electron transport layer 20, so as to prepare a perovskite absorption layer 30 on the electron transport layer 20.

[0065] The step of uniformly coating the second charge transport layer solution onto the surface of the transparent conductive substrate 10 using a slit coating process to obtain the electron transport layer 20 includes: Add 5g of urea to 400ml of pure water and sonicate to obtain a urea solution, wherein the resistance of the pure water is greater than 18MΩ.

[0066] 100 μl of mercaptoacetic acid, 5 ml of concentrated hydrochloric acid (37 wt%), and 1.096 g of stannous chloride dihydrate were added sequentially to the urea solution and mixed thoroughly to obtain a tin dioxide solution.

[0067] Refrigerate the tin dioxide solution for 6-48 hours. The electron transport layer solution was obtained by diluting 200 μl of tin dioxide solution with 1 ml of pure water.

[0068] The electron transport layer solution is uniformly coated onto the surface of the transparent conductive substrate 10 using a slot coating process to obtain a semi-wet electron transport layer film.

[0069] The semi-finished product coated with the electron transport layer semi-wet film is annealed to obtain the electron transport layer 20 stacked on the surface of the transparent conductive substrate 10.

[0070] The perovskite precursor is uniformly coated on the surface of the electron transport layer 20 using a slot coating process to obtain the perovskite absorption layer 30, so as to prepare a passivation / hole transport composite layer 40 on the perovskite absorption layer 30.

[0071] The step of uniformly coating the perovskite precursor onto the surface of the electron transport layer 20 using a slot coating process to obtain the perovskite absorber layer 30 includes: The perovskite precursor is uniformly coated on the surface of the electron transport layer 20 using a slot coating process to obtain a semi-wet perovskite absorber layer 30.

[0072] The perovskite absorber layer 30 is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer 30.

[0073] In the embodiments of this application, the thickness of the metal electrode 50 is between 80nm and 120nm. That is to say, the thickness of the metal electrode 50 can be 80nm or 120nm, or any value between 80nm and 120nm, such as 82nm, 85nm, 88nm, 91nm, 93nm, 97nm, 99nm, 105nm, 110nm, 115nm, etc., which will not be listed here.

[0074] In embodiments of this application, after the passivation / charge transport composite layer is obtained by coating the mixed solution precursor onto the surface of the perovskite absorber layer 30, the preparation method further includes the following steps: The above semi-finished product is subjected to P2 scribing treatment so that the laser can accurately etch through the passivation / hole transport composite layer 40, perovskite absorption layer 30 and electron transport layer 20 above, and expose the transparent conductive oxide layer on the transparent conductive glass, without damaging the transparent glass substrate. This provides a channel for the subsequent preparation of metal electrode 50, so that the top electrode of each sub-cell can directly contact and conduct the bottom electrode (i.e. transparent conductive oxide layer) of the next sub-cell, thereby realizing vertical series interconnection.

[0075] A metal electrode 50 is sputtered onto the passivation / charge transport composite layer.

[0076] A P3 scribing process is performed on the metal electrode 50 to allow the laser to precisely etch through the upper metal electrode 50, the passivation / hole transport composite layer 40, the perovskite absorption layer 30, and the electron transport layer 20, exposing the transparent conductive oxide layer on the transparent conductive glass, thereby forming an isolation groove to cut off the lateral connection between the top electrodes of adjacent sub-cells, completing the final electrical isolation of the sub-cells, and ensuring that the current can only flow in series along the path of "P1 isolation region → P2 conduction region → P3 isolation region".

[0077] Example 1 Example 1: The fabrication method of the formal perovskite solar cell 100 is as follows: At 300mm P1 laser scribing is performed on a 300mm transparent conductive glass according to the target pattern. The etching depth of the laser scribing is such that the corresponding conductive layer is removed.

[0078] After marking the transparent conductive glass with P1, ultrasonically clean it for 15 minutes each with cleaning agent, deionized water, and ethanol solvent, and then dry it with a nitrogen gun for later use.

[0079] Add 5g of urea to 400mL of pure water (resistance > 18MΩ), sonicate to dissolve, then add 100μL of mercaptoacetic acid and 5mL of concentrated hydrochloric acid (37wt%) sequentially. Finally, add 1.096g of stannous chloride dihydrate (SnCl2·2H2O), mix thoroughly, and refrigerate for 6-48 hours. Take 200μL of SnO2 stock solution and add it to 1mL of pure water, sonicate to mix thoroughly to form a 0.002M SnO2 dilution.

[0080] The prepared tin oxide dilution solution was uniformly coated onto a clean FTO substrate using a slot coating method, and the electron transport layer 20 was obtained after annealing.

[0081] The prepared perovskite precursor was uniformly coated onto a tin oxide substrate that had been UV-cleaned using a slot coating method. After vacuuming and annealing, the perovskite absorber layer 30 was obtained.

[0082] Dissolve 30-60 mg / mL of isobutylammonium bromide (i-BABr) in isopropanol to obtain a passivation solution. After complete dissolution by shaking, the solution is ready for use.

[0083] Dissolve the hole transport material used in the formal structure (such as Spiro or PTAA) in anisole or chlorobenzene at a concentration of 20-100 mg / mL, and allow it to dissolve completely by shaking before use. The concentration of the hole transport material used in the formal structure dissolved in anisole or chlorobenzene can be 20 mg / mL or 100 mg / mL, or any concentration between 20-100 mg / mL, such as 21 mg / mL, 25 mg / mL, 29 mg / mL, 30 mg / mL, 33 mg / mL, 39 mg / mL, 45 mg / mL, 55 mg / mL, 62 mg / mL, 70 mg / mL, 75 mg / mL, 80 mg / mL, 88 mg / mL, 90 mg / mL, 97 mg / mL, etc., and will not be listed here.

[0084] The prepared passivation solution is added to the prepared hole transport material solution at a concentration of 0.5 mg / mL-5 mg / mL. After shaking and dissolving, a mixed solution precursor of passivation / hole transport is obtained for later use. The concentration of the passivation solution added to the hole transport layer solution can be 0.5 mg / mL or 5 mg / mL, or any concentration between 0.5 and 5 mg / mL, such as 0.51 mg / mL, 0.86 mg / mL, 1.2 mg / mL, 1.88 mg / mL, 2.3 mg / mL, 2.77 mg / mL, 3.41 mg / mL, 3.95 mg / mL, 4.49 mg / mL, 4.95 mg / mL, etc., which will not be listed here.

[0085] The composite solution of the two-dimensional perovskite and hole transport layer was uniformly coated on the perovskite absorber layer 30 by a slit coating method, and after annealing, the composite layer of two-dimensional perovskite and hole transport layer was obtained.

[0086] The components coated with the hole transport layer composite layer are then subjected to laser P2 treatment.

[0087] The above components are sputtered with metal electrodes 50 and then treated with laser P3 to obtain a complete perovskite solar cell 100 with a formal structure.

[0088] Example 2 Example 2 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with phenylethylammonium bromide (PEABr).

[0089] Example 3 Example 3 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with diamine dihydrobromide (DABr).

[0090] Example 4 Example 4 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with 2-(1-cyclohexenyl)ethylamine hydrobromide (CHEABr).

[0091] Example 5 Example 5 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with methylammonium bromide (MABr).

[0092] Example 6 Example 6 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with tetrabutylammonium bromide (TBAB).

[0093] Example 7 Example 7 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with phenylpropylammonium bromide (PPAABr).

[0094] Example 8 Example 8 describes the preparation of a perovskite solar cell 100 using the same method as in Example 1, except that isobutylammonium bromide (i-BABr) is replaced with butylammonium bromide (BABr).

[0095] Comparative Example 1 Comparative Example 1 prepared a perovskite solar cell 100 according to the method of Example 1, except that the hole transport layer was prepared directly using only the hole transport solution, that is, no passivation material was added to the hole transport layer solution.

[0096] Comparative Example 2 Comparative Example 2 prepared a perovskite solar cell 100 according to the method of Example 1, except that the passivation solution was used to prepare the passivation layer separately, and the hole transport solution was used to prepare the hole transport layer separately. That is, the traditional two-step method was used to prepare the passivation layer and the hole transport layer.

[0097] SEM image of the grain distribution on the passivation layer surface of the perovskite solar cell 100 prepared in Example 1 is shown below. Figure 2 As shown in the figure, the SEM image of the grain distribution on the surface of the perovskite absorber layer 30 of the perovskite solar cell 100 without a passivation layer prepared in Comparative Example 1 is shown in the figure. Figure 3 As shown in the figure, the SEM image of the grain distribution on the surface of the passivation layer of the perovskite solar cell 100 with a passivation layer fabricated separately in Comparative Example 2 is shown in the figure. Figure 4 As shown, the JV curves of the perovskite solar cell 100 with the formal structure obtained in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 5 As shown, the JV curves of the cell modules in the perovskite solar cells 100 with formal structures obtained in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 6 As shown, according to Figure 2-6 It can be seen that: compared with Comparative Example 1 and Comparative Example 2, the Voc and FF of Example 1 are both higher; and although the WPCE of Comparative Example 2 is higher than that of Comparative Example 1, the WPCE of Comparative Example 2 is still lower than that of Example 1 even though it requires more equipment than Example 1 (at least one more slot coating device).

[0098] Figure 7-9 The images shown are PL images of Comparative Example 1, Comparative Example 2, and Example 1, respectively. The excitation light source used in the PL images is 450 nm, and the test sample structure is FTO / SnO2 / PVK or FTO / SnO2 / PVK / passivation layer.

[0099] From the three PL graphs above, it can be concluded that the PL intensity of Example 1 is significantly higher than that of Comparative Example 2, and the PL intensity of Comparative Example 2 is significantly higher than that of Comparative Example 1. Specifically, according to the experimental data, the PL intensity of Example 1 is 4021, the PL intensity of Comparative Example 2 is 2768, and the PL intensity of Comparative Example 1 is 1436.

[0100] Furthermore, combined Figure 2-4 as well as Figure 7-9It can be seen that, based on the SEM images and PL images of Examples 1, 1, and 2, respectively, it can be demonstrated that the passivation layer obtained by the one-step preparation of the passivation / hole transport composite layer 40 of this application has a significantly better effect than the passivation layer prepared alone, and the performance of the perovskite solar cell 100 without a passivation layer.

[0101] In another embodiment of this application, the passivation / charge transport composite layer is a passivation / electron transport composite layer. Therefore, the perovskite solar cell 100 has an inverted structure, that is, the perovskite solar cell 100 includes a transparent conductive substrate 10, a hole transport layer, a perovskite absorber layer 30, a passivation / electron transport composite layer, and a metal electrode 50 stacked sequentially.

[0102] The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: An organic ammonium bromide salt is dissolved in isopropanol solvent, and the solution is shaken to dissolve, resulting in a passivation solution with a concentration of 30-60 mg / mL. The concentration of the passivation solution can be 30 mg / mL or 60 mg / mL, or any concentration between 30-60 mg / mL, such as 31 mg / mL, 36 mg / mL, 42 mg / mL, 48 mg / mL, 53 mg / mL, 57 mg / mL, 59 mg / mL, etc., which will not be listed here.

[0103] [6,6]-phenyl C61 butyrate methyl ester (PC61BM) was dissolved in chlorobenzene solvent, and the solution was shaken to obtain an electron transport layer solution with a concentration of 20-40 mg / mL. The concentration of the electron transport layer solution can be 20 mg / mL or 40 mg / mL, or any concentration between 20-40 mg / mL, such as 21 mg / mL, 23 mg / mL, 34 mg / mL, 37 mg / mL, 39 mg / mL, etc., which will not be listed here.

[0104] The prepared passivation solution is added to the prepared electron transport layer solution at a concentration of 0.5 mg / mL to 5 mg / mL, and the mixture is shaken to dissolve, yielding a mixed solution precursor. The concentration of the passivation solution added to the electron transport layer solution can be 0.5 g / mL or 5 g / mL, or any concentration between 0.5 and 5 g / mL, such as 0.51 g / mL, 0.88 g / mL, 1.26 g / mL, 1.7 g / mL, 1.98 g / mL, 2.29 g / mL, 2.85 g / mL, 3.2 g / mL, 3.7 g / mL, 3.99 g / mL, 4.21 g / mL, 4.68 g / mL, 4.99 g / mL, etc., which will not be listed here.

[0105] By coating the mixed solution precursor onto the surface of the perovskite absorber layer 30, a passivation / electron transport composite layer is obtained. In this passivation / electron transport composite layer, a continuous two-dimensional perovskite can be generated through the reaction of organic ammonium with the surface-rich PbI2. The outer layer of hydrophobic organic carbon chains forms a double-layer protective barrier, scattering sputtered ion kinetic energy and significantly reducing the ion flux reaching the underlying 3D perovskite. This passivates surface / grain boundary defects, inhibits ion migration, constructs a hydrophobic barrier, and optimizes energy level arrangement, thereby improving open-circuit voltage, fill factor, and environmental stability.

[0106] In addition, the two-dimensional perovskite organic ammonium salt uses isopropanol as the main solvent. In the large-area slot coating deposition method, the contact time is longer than in the dynamic spin coating method. If not properly adjusted, IPA can penetrate along grain boundaries, increasing roughness and causing a decrease in carrier mobility and Jsc decay. In contrast, the one-step two-in-one method uses a solvent with extremely low polarity and no hydrogen bonds, which hardly dissolves the complete 3D perovskite bulk. Isopropanol accounts for only a small proportion of this solvent, and its ability to damage the perovskite absorber layer 30 is far weaker than the damage caused by pure isopropanol in the traditional separate preparation of the passivation layer.

[0107] In embodiments of this application, the step of coating the mixed solution precursor onto the surface of the perovskite absorber layer 30 to obtain a passivation / charge transport composite layer includes: The mixed solution precursor is added to a slot coater, and the mixed solution precursor is uniformly coated onto the surface of the perovskite absorber layer 30 at a coating speed of 5-20 mm / s and a dispensing rate of 10-20 μL / s. After the solvent evaporates, a composite solution semi-wet film is obtained. The slot width of the slot coater is 80-150 μm, and the area of ​​the perovskite absorber layer 30 is greater than or equal to 300 μm. 300mm.

[0108] The coating speed can be 5 mm / s or 20 mm / s, or any speed between 5 and 20 mm / s, such as 5.1 mm / s, 5.5 mm / s, 5.9 mm / s, 6.8 mm / s, 9.4 mm / s, 11.3 mm / s, 16 mm / s, 18.5 mm / s, 19.9 mm / s, etc.

[0109] The dispensing rate can be 10 uL / s or 20 uL / s, or any dispensing rate between 10 and 20 uL / s, such as 10.1 uL / s, 10.9 uL / s, 12.5 uL / s, 14 uL / s, 16.2 uL / s, 17 uL / s, 18.8 uL / s, 19.1 uL / s, 19.9 uL / s, etc., which will not be listed here.

[0110] The slit width can be 80 μm or 150 μm, or any width between 80 and 150 μm, such as 80.1 μm, 88 μm, 92 μm, 97 μm, 100 μm, 109 μm, 115 μm, 123 μm, 138 μm, 145 μm, 149 μm, etc., which will not be listed here.

[0111] The area of ​​the perovskite absorber layer can be 300. 300mm, or 300 350mm, 350 350mm, etc., will not be listed here one by one.

[0112] This setup allows for the preparation of the mixed solution precursor in one step, and enables the preparation of a large-area passivation / charge transport composite layer with uniform thickness and stable film structure, significantly improving preparation efficiency and reducing preparation costs.

[0113] The semi-finished product coated with the composite solution semi-wet film is placed on a hot plate at 130-150°C and annealed for 5-10 minutes to obtain a passivation / charge transport composite layer stacked on the surface of a large-area perovskite absorber layer 30, wherein the total thickness of the perovskite absorber layer 30 and the passivation / charge transport composite layer is 500nm-560nm.

[0114] The annealing temperature can be 130℃ or 150℃, or any temperature between 130℃ and 150℃, such as 131℃, 135℃, 138℃, 140℃, 142℃, 146℃, 149℃, etc., which will not be listed here.

[0115] The annealing time can be 5 minutes or 10 minutes, or any time between 5 and 10 minutes, such as 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 8 minutes, 8.5 minutes, 9 minutes, 9.5 minutes, etc., which will not be listed here.

[0116] The total thickness can be 500nm or 560nm, or any thickness between 500 and 560nm, such as 501nm, 507nm, 510nm, 515nm, 525nm, 530nm, 540nm, 550nm, 555nm, 559nm, etc., which will not be listed here.

[0117] In embodiments of this application, before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate 10 after it has been scribing with P1.

[0118] The transparent conductive substrate 10 prepared after P1 scribing and being clean and dry includes: Prepare a transparent conductive substrate 10.

[0119] A P1 line scribing process is performed on the transparent conductive substrate 10.

[0120] The transparent conductive substrate 10 is cleaned in deionized water containing a cleaning agent.

[0121] The transparent conductive substrate 10 is rinsed in deionized water.

[0122] The transparent conductive substrate 10 is ultrasonically cleaned in ethanol for 13-17 minutes. The ultrasonic cleaning time of the transparent conductive substrate 10 in ethanol can be 13 min, 13.5 min, 14 min, 14.5 min, 15 min, 15.5 min, 16 min, 16.5 min, etc., and will not be listed here.

[0123] The transparent conductive substrate 10 was dried with a nitrogen gun.

[0124] Multiple deep cleanings can prevent dirt residue from remaining on the transparent conductive substrate 10 after P1 scribing. Nitrogen gun drying can quickly remove residual solvent / moisture to avoid water stains, prevent surface re-oxidation or adsorption of impurities, thereby ensuring the stability and uniformity of subsequent thin film deposition or device performance.

[0125] A NiOx layer is sputtered on the surface of the transparent conductive substrate 10, and the NiOx layer is a hole transport layer.

[0126] The step of sputtering a NiOx layer on the surface of the transparent conductive substrate 10, wherein the NiOx layer is a hole transport layer, includes: Using oxygen as the sputtering gas, NiOx material is obtained by reactive sputtering of a nickel metal target under both DC and RF methods. The sputtering time is controlled to obtain a hole transport layer of the target thickness deposited on the transparent conductive substrate 10.

[0127] The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain the perovskite absorber layer 30.

[0128] The step of uniformly coating the perovskite precursor onto the surface of the hole transport layer using a slot coating process to obtain the perovskite absorber layer 30 includes: The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain a perovskite absorber layer 30 semi-wet film.

[0129] The perovskite absorber layer 30 is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer 30.

[0130] In embodiments of this application, after the passivation / charge transport composite layer is obtained by coating the mixed solution precursor onto the surface of the perovskite absorber layer 30, the preparation method further includes the following steps: A BCP protective layer is prepared on the passivation / charge transport composite layer using a thermal evaporation method. The thickness of the BCP protective layer is between 5 nm and 10 nm, that is, the thickness of the BCP protective layer can be 5 nm or 10 nm, or any value between 5 nm and 10 nm, such as 6 nm, 7 nm, 7.5 nm, 9 nm, etc., which will not be listed here.

[0131] The following advantages are achieved by further preparing a BCP protective layer on the surface of the passivation / electron transport composite layer: 1. Highly efficient hole blocking: The BCP has a deep HOMO level (approximately -6.0 eV), which can effectively block holes from reaching the cathode and prevent electron-hole recombination at the metal electrode 50 interface, significantly improving the open circuit voltage (VOC) and fill factor (FF).

[0132] 2. Improve ohmic contact: As a buffer layer, it reduces the contact barrier between the electron transport layer 20 (such as PCBM) and the metal electrode 50 (such as Ag, Au), promotes electron extraction, and reduces series resistance.

[0133] 3. Inhibit ion migration and corrosion: The dense BCP layer can physically block the diffusion of halide ions in the perovskite to the metal electrode 50, prevent the metal electrode 50 from being corroded (such as by Ag iodination), and improve the long-term stability of the device.

[0134] 4. Defect passivation and film protection: The nitrogen atoms in the BCP molecule can coordinate with the uncoordinated lead ions on the perovskite surface, further passivating interface defects; at the same time, it avoids high-energy particles directly bombarding the fragile organic / perovskite layer during subsequent thermal evaporation of metal.

[0135] The above semi-finished product is subjected to P2 scribing treatment so that the laser can accurately etch through the hole transport layer, perovskite absorption layer 30 and passivation / electron transport composite layer above, and expose the transparent conductive oxide layer on the transparent conductive glass, without damaging the transparent glass substrate. This provides a channel for the subsequent preparation of the metal electrode 50, so that the top electrode of each sub-cell can directly contact and conduct the bottom electrode (i.e., transparent conductive oxide layer) of the next sub-cell, thereby realizing vertical series interconnection.

[0136] Metal electrodes 50 are sputtered onto the passivation / charge transport composite layer using magnetron sputtering. The thickness of the metal electrode 50 is between 80 nm and 120 nm, that is, the thickness of the metal electrode 50 can be 80 nm or 120 nm, or any value between 80 nm and 120 nm, such as 82 nm, 85 nm, 88 nm, 91 nm, 93 nm, 97 nm, 99 nm, 105 nm, 110 nm, 115 nm, etc., which will not be listed here.

[0137] A P3 scribe line is performed on the metal electrode 50 to allow the laser to precisely etch through the metal electrode 50, hole transport layer, perovskite absorption layer 30, and passivation / electron transport composite layer, exposing the transparent conductive oxide layer on the transparent conductive glass, thereby forming an isolation groove to cut off the lateral connection between the top electrodes of adjacent sub-cells, completing the final electrical isolation of the sub-cells and ensuring that the current can only flow in series along the path of "P1 isolation region → P2 conduction region → P3 isolation region".

[0138] Example 9 Example 9: The fabrication method of the inverse perovskite solar cell 100 is as follows: The transparent conductive glass, after laser P1 treatment, undergoes deep cleaning. The FTO substrate is ultrasonically cleaned for 13-17 minutes in deionized water, deionized water, and ethanol containing cleaning agents, respectively. Finally, the glass surface is dried with a nitrogen gun before use. The ultrasonic cleaning time of the transparent conductive substrate 10 in ethanol can be 13 min, 13.5 min, 14 min, 14.5 min, 15 min, 15.5 min, 16 min, 16.5 min, etc., which will not be listed here.

[0139] O2 was used as the sputtering gas, and NiOx material was obtained by reaction sputtering of a metallic nickel target under both DC and RF methods. The sputtering time was controlled to obtain a NiOx film of the target thickness.

[0140] The prepared perovskite precursor was uniformly coated on a NiOx substrate using a slot coating method, and the perovskite absorber layer 30 was obtained after vacuuming and annealing.

[0141] Dissolve 30-60 mg / mLi-BABr raw material in isopropanol solvent, and after complete shaking and dissolution, complete the preparation of two-dimensional perovskite mother liquor.

[0142] The concentration of i-BABr raw material can be 30 mg / mL or 60 mg / mL, or any concentration between 30 and 60 mg / mL, such as 32 mg / mL, 35.8 mg / mL, 37 mg / mL, 48 mg / mL, 59 mg / mL, etc., which will not be listed here.

[0143] [6,6]-phenyl C61 butyrate methyl ester (PC61BM) was dissolved in chlorobenzene at a concentration of 20-40 mg / mL to form an electron transport layer solution.

[0144] [6,6]-phenyl C61 butyrate methyl ester (PC61BM) can be dissolved in chlorobenzene at concentrations of 20 mg / mL or 40 mg / mL, as well as any concentration between 20 and 40 mg / mL, such as 22 mg / mL, 26.8 mg / mL, 29 mg / mL, 35.2 mg / mL, 39 mg / mL, etc., which will not be listed here.

[0145] The above-mentioned two-dimensional perovskite mother liquor and electron transport layer solution were fused at a concentration of 0.5 mg / mL to 5 mg / mL to form a composite solution, which was then uniformly coated onto the perovskite absorber layer 30 using a slit coating method. After annealing, a two-dimensional perovskite and electron transport layer composite layer was obtained.

[0146] The concentrations mentioned above can be 0.5 g / mL or 5 g / mL, or any concentration between 0.5 and 5 g / mL, such as 0.51 g / mL, 0.78 g / mL, 0.96 g / mL, 1.3 g / mL, 1.88 g / mL, 2.29 g / mL, 3.05 g / mL, 3.82 g / mL, 4.24 g / mL, 4.59 g / mL, 4.71 g / mL, 4.88 g / mL, 4.99 g / mL, etc., which will not be listed here one by one.

[0147] A BCP protective layer is prepared on the composite layer by thermal evaporation, with a thickness of 5 nm or 10 nm, or any value between 5 and 10 nm, such as 5.1 nm, 5.8 nm, 7 nm, 8 nm, 9 nm, 9.9 nm, etc., which will not be listed here.

[0148] The above components are subjected to laser P2 treatment.

[0149] Finally, Ag metal electrodes 50 with a thickness of 80-120 nm were fabricated using magnetron sputtering. After laser P3 treatment, a complete inverted perovskite solar cell 100 module was obtained. That is to say, the thickness of the metal electrode 50 can be 80 nm or 120 nm, or any value between 80 nm and 120 nm, such as 82 nm, 85 nm, 88 nm, 91 nm, 93 nm, 97 nm, 99 nm, 105 nm, 110 nm, 115 nm, etc., which will not be listed here.

[0150] Example 10 Example 10 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that i-BABr is replaced with PEABr.

[0151] Example 11 Example 11 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that i-BABr is replaced with DABr.

[0152] Example 12 Example 12 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that i-BABr is replaced with 2-(1-cyclohexenyl)ethylamine hydrobromide (CHEABr).

[0153] Example 13 Example 13 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that isobutylammonium bromide (i-BABr) is replaced with methylammonium bromide (MABr).

[0154] Example 14 Example 14 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that isobutylammonium bromide (i-BABr) is replaced with tetrabutylammonium bromide (TBAB).

[0155] Example 15 Example 15 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that isobutylammonium bromide (i-BABr) is replaced with phenylpropylammonium bromide (PPAABr).

[0156] Example 16 Example 16 describes the preparation of a perovskite solar cell 100 using the same method as in Example 9, except that isobutylammonium bromide (i-BABr) is replaced with butylammonium bromide (BABr).

[0157] Comparative Example 3 Comparative Example 3 prepared a perovskite solar cell 100 according to the method of Example 9, except that the electron transport layer 20 was prepared directly using only an electron transport solution, that is, no passivation material was added to the electron transport layer solution.

[0158] Comparative Example 4 Comparative Example 4 prepared a perovskite solar cell 100 according to the method of Example 9, except that the passivation solution was used to prepare the passivation layer separately, and the electron transport solution was used to prepare the electron transport layer 20 separately. That is, the passivation layer and the electron transport layer 20 were prepared by the traditional two-step method.

[0159] Please see Figure 1-9As shown, in a second aspect, this application also provides a perovskite solar cell 100, which is prepared by the above-described method for preparing perovskite solar cells 100. Therefore, the perovskite solar cell 100 has all the above-described beneficial effects, which will not be repeated here.

[0160] For ease of description, spatial relative terms such as "above," "on top of," "on the upper surface of," "above," etc., are used herein to describe the spatial positional relationship of a device or feature as shown in the figures to other devices or features. It should be understood that spatial relative terms are intended to encompass different orientations in use or operation beyond the orientation of the device as described in the figures. For example, if the device in the figures were inverted, a device described as "above" or "on top of" other devices or structures would subsequently be positioned as "below" or "under" other devices or structures. Thus, the exemplary term "above" can include both "above" and "below." The device may also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used herein will be interpreted accordingly.

[0161] Furthermore, it should be noted that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be construed as limiting the scope of protection of this application.

[0162] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing a perovskite solar cell, characterized in that, The preparation steps include the following: A mixed solution precursor is obtained by mixing the passivation solution with the first charge transport layer solution. The mixed solution precursor is coated onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer.

2. The method for preparing a perovskite solar cell according to claim 1, characterized in that, The passivation / charge transport composite layer is a passivation / hole transport composite layer; The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: The organic ammonium bromide salt was dissolved in isopropanol solvent, and the solution was shaken to dissolve it, resulting in a passivation solution with a concentration of 30-60 mg / mL. Spiro-OMeTAD or PTAA was dissolved in anisole or chlorobenzene solvent, and the solution was shaken to dissolve, resulting in a hole transport layer solution with a concentration of 20-100 mg / mL. The prepared passivation solution was added to the prepared hole transport layer solution at a concentration of 0.5 mg / mL-5 mg / mL, and the mixture was shaken to dissolve, thus obtaining the mixed solution precursor.

3. The method for preparing a perovskite solar cell according to claim 1, characterized in that, The passivation / charge transport composite layer is a passivation / electron transport composite layer; The step of mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor includes: The organic ammonium bromide salt was dissolved in isopropanol solvent, and the solution was shaken to dissolve it, resulting in a passivation solution with a concentration of 30-60 mg / mL. [6,6]-phenyl C61 butyrate methyl ester (PC61BM) was dissolved in chlorobenzene solvent, and the solution was shaken to obtain an electron transport layer solution with a concentration of 20-40 mg / mL. The prepared passivation solution was added to the prepared electron transport layer solution at a concentration of 0.5 mg / mL-5 mg / mL, and the mixture was shaken to dissolve, thus obtaining the mixed solution precursor.

4. The method for preparing a perovskite solar cell according to any one of claims 1-3, characterized in that, The step of coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer includes: The mixed solution precursor is added to a slot coater, and the mixed solution precursor is uniformly coated onto the surface of the perovskite absorber at a coating speed of 5-20 mm / s and an outflow rate of 10-20 μL / s. After the solvent evaporates, a composite solution semi-wet film is obtained. The slot width of the slot coater is 80-150 μm, and the area of ​​the perovskite absorber is greater than or equal to 300 μm. 300mm; The semi-finished product coated with the composite solution semi-wet film is placed on a hot plate at 130-150°C and annealed for 5-10 minutes to obtain a passivation / charge transport composite layer stacked on the surface of a large-area perovskite absorber layer, wherein the total thickness of the perovskite absorber layer and the passivation / charge transport composite layer is 500nm-560nm.

5. The method for preparing a perovskite solar cell according to claim 2 or 3, characterized in that, The organic ammonium bromide salt is selected from any one of isobutylammonium bromide (i-BABr), phenylethylammonium bromide (PEABr), diamine dihydrobromide (DABr), 2-(1-cyclohexenyl)ethylamine hydrobromide (CHEABr), methylammonium bromide (MABr), tetrabutylammonium bromide (TBAB), phenylpropylammonium bromide (PPAABr), and butylammonium bromide (BABr).

6. The method for preparing a perovskite solar cell according to claim 1 or 2, characterized in that, Before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate that has been scribing with P1. The second charge transport layer solution is uniformly coated onto the surface of the transparent conductive substrate using a slit coating process to obtain an electron transport layer. The perovskite precursor is uniformly coated on the surface of the electron transport layer using a slot coating process to obtain the perovskite absorption layer. And / or, after the preparation method involves coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer, the preparation method further includes the following steps: Perform P2 marking on the above semi-finished products; A metal electrode is sputtered onto the passivation / charge transport composite layer; P3 scribing is performed on the metal electrode.

7. The method for preparing a perovskite solar cell according to claim 6, characterized in that, The preparation of the clean and dry transparent conductive substrate after P1 scribing includes: Prepare a transparent conductive substrate; A P1 line scribing process is performed on the transparent conductive substrate; The transparent conductive substrate is cleaned by immersing it in deionized water containing a cleaning agent; The transparent conductive substrate is rinsed in deionized water. The transparent conductive substrate was ultrasonically cleaned in ethanol for 13-17 minutes. The transparent conductive substrate was dried using a nitrogen gun. And / or, the step of uniformly coating the second charge transport layer solution onto the surface of the transparent conductive substrate using a slit coating process to obtain an electron transport layer includes: Add 5g of urea to 400ml of pure water and sonicate to obtain a urea solution, wherein the resistance of the pure water is greater than 18MΩ. 100 μl of mercaptoacetic acid, 5 ml of concentrated hydrochloric acid (37 wt%) and 1.096 g of stannous chloride dihydrate were added to the urea solution in sequence and mixed evenly to obtain a tin dioxide solution. Refrigerate the tin dioxide solution for 6-48 hours. The electron transport layer solution was obtained by diluting 200 μl of tin dioxide solution with 1 ml of pure water. The electron transport layer solution is uniformly coated onto the surface of the transparent conductive substrate using a slit coating process to obtain a semi-wet electron transport layer film. The semi-finished product coated with the electron transport layer semi-wet film is annealed to obtain an electron transport layer stacked on the surface of a transparent conductive substrate. And / or, the process of uniformly coating the perovskite precursor onto the surface of the electron transport layer using a slot coating process to obtain the perovskite absorber layer includes: The perovskite precursor is uniformly coated on the surface of the electron transport layer using a slot coating process to obtain a semi-wet perovskite absorber layer. The perovskite absorber layer is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer. And / or, the thickness of the metal electrode is between 80 nm and 120 nm.

8. The method for preparing a perovskite solar cell according to claim 1 or 3, characterized in that, Before mixing the passivation solution with the first charge transport layer solution to obtain the mixed solution precursor, the preparation method further includes the following steps: Prepare a clean and dry transparent conductive substrate that has been scribing with P1. A NiOx layer is sputtered onto the surface of the transparent conductive substrate, wherein the NiOx layer is a hole transport layer; The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain the perovskite absorption layer. And / or, after the preparation method involves coating the mixed solution precursor onto the surface of the perovskite absorber layer to obtain a passivation / charge transport composite layer, the preparation method further includes the following steps: A BCP protective layer was prepared on the passivation / charge transport composite layer using a thermal evaporation method. Perform P2 marking on the above semi-finished products; Metal electrodes were sputtered onto the passivation / charge transport composite layer using magnetron sputtering. P3 scribing is performed on the metal electrode.

9. The method for preparing a perovskite solar cell according to claim 8, characterized in that, The preparation of the clean and dry transparent conductive substrate after P1 scribing includes: Prepare a transparent conductive substrate; A P1 line scribing process is performed on the transparent conductive substrate; The transparent conductive substrate is cleaned by immersing it in deionized water containing a cleaning agent; The transparent conductive substrate is rinsed in deionized water. The transparent conductive substrate was ultrasonically cleaned in ethanol for 13-17 minutes. The transparent conductive substrate was dried using a nitrogen gun. And / or, the sputtering of a NiOx layer on the surface of the transparent conductive substrate, wherein the NiOx layer is a hole transport layer, includes: Using oxygen as the sputtering gas, NiOx material is obtained by reactive sputtering of a metallic nickel target under both DC and RF methods. The sputtering time is controlled to obtain a hole transport layer of target thickness deposited on the transparent conductive substrate. And / or, the step of uniformly coating the perovskite precursor onto the surface of the hole transport layer using a slot coating process to obtain the perovskite absorber layer includes: The perovskite precursor is uniformly coated on the surface of the hole transport layer using a slot coating process to obtain a semi-wet perovskite absorber layer. The perovskite absorber layer is obtained by vacuuming and annealing the semi-wet film of the perovskite absorber layer. And / or, the thickness of the BCP protective layer is between 5nm and 10nm; And / or, the thickness of the metal electrode is between 80 nm and 120 nm.

10. A perovskite solar cell, characterized in that, The perovskite solar cell was prepared using the method described in any one of claims 1-9.